1992
DOI: 10.1080/15287399209531608
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and reproductive effects of 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin in ring‐necked pheasant hens

Abstract: Hen pheasants (Phasianus colchicus) injected with graded single doses of TCDD (6.25, 25, or 100 micrograms/kg) exhibited delayed-onset body weight loss and mortality--classic signs of the wasting syndrome. The lowest single dose of TCDD to produce this effect was 25 micrograms/kg. When hen pheasants were treated weekly with far lower doses of TCDD (0.01-1.0 microgram/kg/wk) for 10 wk, signs of the wasting syndrome and mortality were also produced. The lowest cumulative TCDD dose required to produce the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 20 publications
2
51
1
Order By: Relevance
“…All PCB concentrations were less than conservative wildlife guidelines (100-110 ng/g) available for fish (IJC 1987;Newell et al 1987). TCDD-EQ was less than or equal to the LOD (1.7 pg/g) in all samples (i.e., dioxin-like activity was not detected in any sample), and all TCDD-EQs were less than the dietary toxicity thresholds for mammals (4.4 pg/g; Heaton et al 1995;Tillitt et al 1996) and birds (5.0 pg/g; Nosek et al 1992). …”
Section: Organochlorine Pesticides Total Pcbs and H4iie-derived Diomentioning
confidence: 96%
“…All PCB concentrations were less than conservative wildlife guidelines (100-110 ng/g) available for fish (IJC 1987;Newell et al 1987). TCDD-EQ was less than or equal to the LOD (1.7 pg/g) in all samples (i.e., dioxin-like activity was not detected in any sample), and all TCDD-EQs were less than the dietary toxicity thresholds for mammals (4.4 pg/g; Heaton et al 1995;Tillitt et al 1996) and birds (5.0 pg/g; Nosek et al 1992). …”
Section: Organochlorine Pesticides Total Pcbs and H4iie-derived Diomentioning
confidence: 96%
“…Although many studies with young or adult birds have shown dioxinlike toxic and biochemical effects of TCDD and PCBs, these studies were not designed for REPs of compounds to be reliably derived (56)(57)(58)(59)(60)(61)(62)(63). At present, TEFs for birds can only be derived from egg injection studies, studies with cultured avian hepatocytes, and studies with cultured thymus cells.…”
Section: Tefs For Birdsmentioning
confidence: 99%
“…This is approximately 236 times greater than the NOAEC values that we used in our hazard assessment, 16.5 times greater than the NOAEC values for pheasants (49), and approximately 165 times greater than the NOAEC values in white leghorn chicken eggs (50). Since these values were determined with the H4IIE assay used in our studies (25), the values are directly comparable to those reported here.…”
Section: Results Of Hazard Assessmentmentioning
confidence: 92%
“…Our value is approximately 16-fold less than that derived by the U.S. EPA in their guidance document for hazard assessments of the effects of 2,3,7,8-TCDD on wildlife, but is in the range of values predicted from studies of other species (42). The U.S. EPA determined that a concentration of 6 ng TCDD/kg in fish would be associated with little hazard to fish-eating birds, based on assumptions about the proportions of fish in the diet and the BMF values and the NOAEC value of 100 ng 2,3,7,8-TCDD/kg in ringnecked pheasant (Phasianus colchicus) eggs (49). Based on the BMF value of 19 that we have used in our study, this would be equivalent to approximately 114 ng/kg in the eggs of bald eagles.…”
Section: Results Of Hazard Assessmentmentioning
confidence: 99%